2021
DOI: 10.1007/s42247-021-00197-3
|View full text |Cite
|
Sign up to set email alerts
|

An updated review on boron removal from water through adsorption processes

Abstract: Boron is an essential micronutrient that has raised much interest, given the narrow balance between its necessity and toxicity. Both natural and anthropogenic emissions of boron into water sources can eventually deteriorate water quality and endanger the ecosystem. In this review, we first present a general outline of the importance of boron, boron chemistry in water, boron contamination, and its consequences followed by the recent progress in boron removal methods based on adsorption. The adsorbents for debor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 119 publications
(116 reference statements)
1
19
0
Order By: Relevance
“…The intensity of sorption (1/ n ) values for all transition metals was less than unity indicating the involvement of heterogeneous sites only whereas for B sorption, the 1/ n values were invariably greater than unity plausibly indicating a case of cooperative adsorption. 45 A similar case was also noted for S sorption, especially for phyto-biochars pyrolyzed at 450 °C. The highest desorption capacity () for Zn (61.752 mmol kg −1 ), Fe (346.669 mmol kg −1 ) and Mn (80.591 mmol kg −1 ) was recorded with W450 while the highest for Cu (68.727 mmol kg −1 ), B (90.786 mmol kg −1 ) and S (1698.825 mmol kg −1 ) was observed with L450.…”
Section: Resultssupporting
confidence: 59%
“…The intensity of sorption (1/ n ) values for all transition metals was less than unity indicating the involvement of heterogeneous sites only whereas for B sorption, the 1/ n values were invariably greater than unity plausibly indicating a case of cooperative adsorption. 45 A similar case was also noted for S sorption, especially for phyto-biochars pyrolyzed at 450 °C. The highest desorption capacity () for Zn (61.752 mmol kg −1 ), Fe (346.669 mmol kg −1 ) and Mn (80.591 mmol kg −1 ) was recorded with W450 while the highest for Cu (68.727 mmol kg −1 ), B (90.786 mmol kg −1 ) and S (1698.825 mmol kg −1 ) was observed with L450.…”
Section: Resultssupporting
confidence: 59%
“…This could reflect the known strong Li affinity for Fe-oxyhydroxide surfaces (Wimpenny et al, 2010a) and the lack of reactivity of B species on the positively charged surface of Fe-oxyhydroxides (Kosmulski, 2002(Kosmulski, , 2016. Finally, the B/Li ratio in the detrital sediment fraction roughly corresponds to the B/Li crustal value, while both dissolved B and Li species are not partitioned onto surfaces of detrital minerals during authigenic processes (Bhagyaraj et al, 2021), as observed in Fig. 5D.…”
Section: B and LI Reactions Onto Mineral Surfacesmentioning
confidence: 82%
“…A key aspect influencing the removal of boron from water is its pH. Several investigators [24][25][26][27] have studied the effect of pH; optimum pH appears to be in the range of 8-10, where boron is present in negatively charged ionic form and borates predominate. B(OH) 3 prevails at lower pH, while B(OH) 4 prevails at pH greater than 8.…”
Section: Effect Of Phmentioning
confidence: 99%